Proceedings of the 20th International Conference on Human-Computer Interaction With Mobile Devices and Services 2018
DOI: 10.1145/3229434.3229441
|View full text |Cite
|
Sign up to set email alerts
|

Typical phone use habits

Abstract: Not all smartphone owners use their device in the same way. In this work, we uncover broad, latent patterns of mobile phone use behavior. We conducted a study where, via a dedicated logging app, we collected daily mobile phone activity data from a sample of 340 participants for a period of four weeks. Through an unsupervised learning approach and a methodologically rigorous analysis, we reveal five generic phone use profiles which describe at least 10% of the participants each: limited use, business use, power… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 40 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…We observed that no objective measures of use (screen time or pickups) nor time estimates load with any mental health measure or the SAS at the individual item level in our EFA. This further demonstrates a lack of any clear relationship between objective screen time and health or well-being (Ellis et al, 2019;Johannes et al, 2019;Katevas, Arapakis, & Pielot, 2018;Orben, Dienlin, & Przybylski, 2019;.…”
Section: Discussionmentioning
confidence: 92%
“…We observed that no objective measures of use (screen time or pickups) nor time estimates load with any mental health measure or the SAS at the individual item level in our EFA. This further demonstrates a lack of any clear relationship between objective screen time and health or well-being (Ellis et al, 2019;Johannes et al, 2019;Katevas, Arapakis, & Pielot, 2018;Orben, Dienlin, & Przybylski, 2019;.…”
Section: Discussionmentioning
confidence: 92%
“…The increasing global prevalence of smartphone use among individuals of all ages demands further research attention. In this sense, current literature points out to at least two broad demands: (1) a focus on transdiagnostic variables, that is, variables Table 5 Moderation analysis examining the interaction between use for entertainment and emotion suppression in the association between amount of use and functional impairment (Elhai et al 2019a), and (2) investigating positive associations between smartphone use and mental health variables, complementing knowledge on problematic use (David et al 2018;Katevas et al 2018). The present study sought to contribute to the efforts towards filling both these gaps.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Panova and Carbonell (2018), most studies on smartphone addiction are based on behaviors which do not support the existence of an addiction disorder. Moreover, a study by Katevas et al (2018) shows that the use of the device for long hours does not necessarily imply a problematic behavior. As noted by Montag et al (2019), there is still neither consensus on the definition of what should be the criteria to reflect a disorder related to smartphones nor a consolidated understanding of what constitutes a problematic behavior in this area.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is only one study that combined objective smartphone use with experience sampling. Katevas, Arapakis, and Pielot (2018) found that phone use at night, not general phone use, negatively predicted well-being. However, the analysis aggregated phone use and well-being per day, rather than predicting each instance of reported well-being with preceding phone use variables.…”
Section: The Current Studymentioning
confidence: 92%